Pendampingan Kemandirian Anak dalam Kewirausahaan di Lembaga Kesejahteraan Sosial Anak (LKSA) Kedungturi Sidoarjo - Sutono Sutono; Ach. Kusnan Arif (FKIP, Universitas Palangka Raya, 2024)
Independence and life skills are needed in a social welfare institution; Al-amin's children (LKSA) have only been able to survive by depending on financial sources from the provision of Zakat, Infaq and Sadaqah from the Benefactors. Independence and life skills in the form of entrepreneurial skills will form a mature entrepreneurial spirit in the children who are in a dormitory which will ultimately lead them to independent living and can even make life easier for the institution where they live. A weak spirit of independence is experienced at the Al-Amin Child Welfare Institution (LKSA), Kedungturi Taman Sidoarjo Village. As productive young people, children in orphanages should have the potential to develop better, but due to limited entrepreneurial knowledge they have they have not been able to develop optimally. This program aims to create independent young entrepreneurs who are able to create business opportunities for orphanages and the surrounding community. The results achieved in the Science and Technology for Society program are making creatively designed stitches and unique shirts, increasing children's resources so they are able to produce, mastering effective marketing strategies and mastering business management.